The effect of a fatiguing exercise by the index finger on single- and multi-finger force production tasks - Danion, F. (2001)
We studied the effects of fatigue, induced by a 60-s maximal isometric force production with the index finger, on multi-finger coordination and force production by the other fingers of the hand. Finger forces were measured during single- and multi-finger maximal voluntary force production (MVC) at two sites, the middle of the distal or the middle of the proximal phalanges. Two fatiguing exercises involving force production by the index finger were used, one at the distal phalanx and the other at the proximal phalanx. The MVC of the index finger dropped by about 33% when it was produced at the site involved in the fatiguing exercise. In addition, large transfer effects of fatigue were observed across sites of force application and across fingers. Force deficit increased under fatigue, especially due to a drop in the recruitment of the index finger. Under fatigue, the index finger was less enslaved during force production by other fingers. During multi-finger tasks, the percentage of total force produced by the index finger was significantly reduced after the fatiguing exercise. The principle of minimization of secondary moments was violated under fatigue. We suggest that the most impaired (fatigued) finger shows less interaction with other fingers or, in other words, is being progressively removed from the multi-finger synergy. Some of the observed changes in finger coordination suggest effects of fatigue at a central (neural) level.